PENGARUH TATA KELOLA PERUSAHAAN, LIKUIDITAS, DAN LEVERAGE TERHADAP KESULITAN KEUANGAN - Janah, Diah Oktavianti; Salim, Ubud (Jurnal Management Risiko dan Keuangan, 2022)
This study aims to analyze the effect of corporate governance using proxies of managerial ownership, institutional ownership, size of the board of directors, size of the board of commissioners and liquidity using proxies of current ratio and leverage using proxies of debt to total asset ratio on financial distress. The sample in this study used company in the textile and garment industry subsector listed on the Indonesia Stock Exchange (IDX) in the 2018 - 2020 period. The sampling in this study used the purposive sampling method, and obtained a sample of 13 textile and garment companies with a total sample of 39 samples. The data analysis method used classical assumption test, multiple linear regression analysis, and hypothesis testing (F test, T-test, and coefficient of determination) using the SPSS 25 program. The results of this study indicate that the managerial ownership has no significant effect on financial distress, institutional ownership has no significant effect on financial distress, size of the board of directors has no significant effect on financial distress, size of the board of commissioners has no significant effect on financial distress, current ratio has significant effect on financial distress, debt to total asset ratio has significant effect on financial distress.